The Relationship of Zink and Iron Levels with Blood Pressure in Pulmonary Tuberculosis Patient - Dewi Kurniasih; Muslina Muslina; Aminahtun Latifah; Dina Afrianti (Jaringan Laboratorium Medis, 2023)
Background: Mycobacterium tuberculosis infection in Tuberculosis (TBC) causes narrowing of the pulmonary blood vessels and triggers pulmonary hypertension which is associated with iron deficiency and anemia. The mineral zinc (Zn) is known to play an important role in destroying the bacteria that cause TBC. In addition, iron (Fe) deficiency in TBC patients can cause relapse and even treatment failure. This study aims to examine the relationship between serum zinc and iron levels and blood pressure in pulmonary TBC patients. Method: A descriptive analytical observational study with a cross sectional design was conducted on 51 TBC patients undergoing treatment at the Simpang IV Sipin Community Health Center, Jambi City. Using a purposive sampling technique, respondents who met the research inclusion and exclusion criteria were examined for zinc and Fe levels. The examination was carried out at the Jambi Province Regional Health Laboratory, the examination result data was then analyzed bivariately using the chi square test. Results: The results of statistical analysis between blood pressure and Zn levels obtained a significant value with P value = 0.877 and a significant value for Fe levels obtained P value = 0.841 ( 0.05). Conclusion: There is no significant relationship between Zn and Fe levels and blood pressure in pulmonary TBC patients. Based on research, it is known that iron deficiency and anemia are not directly related to pulmonary hypertension which can be experienced by TBC patients.